2021
DOI: 10.3389/fmicb.2021.719112
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Environmentally Acquired Bacterial Symbionts for the Squash Bug (Anasa tristis), a Significant Agricultural Pest

Abstract: Most insects maintain associations with microbes that shape their ecology and evolution. Such symbioses have important applied implications when the associated insects are pests or vectors of disease. The squash bug, Anasa tristis (Coreoidea: Coreidae), is a significant pest of human agriculture in its own right and also causes damage to crops due to its capacity to transmit a bacterial plant pathogen. Here, we demonstrate that complete understanding of these insects requires consideration of their association… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 68 publications
0
29
0
Order By: Relevance
“…M4 colonization data were not available for these strains, which appear to be representatives of one unnamed species or two closely related unnamed sister species. However, surprisingly, we found that insects colonized with SL2Y3 or Sq4a are comparable to insects infected with other strains in terms of development time and mass at adulthood ( 27 , 40 ). This indicates that not all genes in the genomic region—and not even all genes found to be upregulated during symbiosis—are required for effective symbiosis.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…M4 colonization data were not available for these strains, which appear to be representatives of one unnamed species or two closely related unnamed sister species. However, surprisingly, we found that insects colonized with SL2Y3 or Sq4a are comparable to insects infected with other strains in terms of development time and mass at adulthood ( 27 , 40 ). This indicates that not all genes in the genomic region—and not even all genes found to be upregulated during symbiosis—are required for effective symbiosis.…”
Section: Discussionmentioning
confidence: 53%
“…This tree indicates that the contiguous genomic region is found only within SBE and PBE Burkholderia and is absent in other members of Burkholderiaceae . Interestingly, this includes the genera Pandoraea and Cupriavidus , even though these are capable of colonizing the M4 ( 15 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous survey of Caballeronia symbionts in stinkbugs revealed region-specific infection with species of the two subgroups: SBE-α was more likely to be detected in Japanese and American stinkbug species of Coreoidea (Kikuchi et al, 2005(Kikuchi et al, , 2011bOlivier-Espejel et al, 2011;Garcia et al, 2014;Kuechler et al, 2016;Ohbayashi et al, 2019b;Acevedo et al, 2021;Hunter et al, 2022), and SBE-β in European species of Coreoidea (Kuechler et al, 2016;Ohbayashi et al, 2019b). However, since only a few insect species have been investigated, and even fewer species from a wide geographic distribution, it remains unclear whether region-specific infection is general.…”
mentioning
confidence: 99%
“…Gut microorganisms provide essential nutrients, digest indigestible food materials, and/or degrade phytotoxins and insecticides ( Kikuchi et al , 2012 ; Engel and Moran, 2013 ; Salem et al , 2014 ; Sudakaran et al , 2017 ; Itoh et al , 2018 ; Moran et al , 2019 ). Many species of stinkbugs in the superfamily Coreoidea (Hemiptera: Heteroptera) develop numerous crypts at the posterior part of the midgut, wherein specific Caballeronia symbionts (previously included in the genus Burkholderia ) densely proliferate - generally as a single species - until almost full occupation of the luminal space ( Kikuchi et al , 2005 , 2011a ; Olivier-Espejel et al , 2011 ; Garcia et al , 2014 ; Kuechler et al , 2016 ; Takeshita and Kikuchi, 2017 ; Ohbayashi et al , 2019b ; Acevedo et al , 2021 ; Hunter et al , 2022 ). Caballeronia gut symbionts play important roles in their hosts, such as the recycling of metabolic waste materials and providing essential amino acids and vitamins, thereby enhancing the growth and fecundity of stinkbugs ( Kikuchi et al , 2007 ; Kikuchi and Fukatsu, 2014 ; Ohbayashi et al , 2019a ).…”
mentioning
confidence: 99%